Dietary Adherence and Glycemic Status among Type 2 Diabetes Patients in Rural Areas (Medicine Today, 2025)
Introduction: The prevalence of diabetes is rising sharply in rural areas, largely due to changes in lifestyle and dietary habits. Enhancing quality of life and preventing acute metabolic disorders as well as long-term effects by reducing premature morbidity and mortality is the core target of therapy for individuals with type 2 diabetes mellitus (T2DM). Aims and Objectives: To assess the level of adherence to dietary recommendations (DRs) among T2DM patients in rural areas and the glycemic status among them. Materials and Methods: This cross-sectional study was conducted among 228 purposively selected, diagnosed T2DM patients who attended the outpatient department of the Pirojpur Diabetic Association in Barisal from January to December 2023. Face-to-face interviews were used to collect data using a pretested, semi-structured questionnaire. Results: The study participants were adult patients with T2DM, with a mean age of 54.7±11.7 years. The mean duration of diabetes was 7.5±6.4 years. The study revealed that only 30.7% of participants had good adherence to DRs, while the majority (69.3%) had poor adherence. Furthermore, 35.5% of participants had good glycemic control, whereas 64.5% had poor glycemic status. Conclusion: Poor adherence contributes to poor glycemic control. Therefore, it is crucial to implement effective measures to improve adherence to DRs and enhance glycemic management. These steps will ultimately help prevent diabetic complications and reduce diabetes-related costs for rural residents.Medicine Today 2025, Vol.37 (1): 127-132